An unusual case of giant aneurysm of the noncoronary sinus of Valsalva with rupture into the left ventricular outflow tract along with distortion of the mitral valve. Issue 9 (19th June 2018) - Tan, Yuying; Xu, Hui; Gao, Yongsheng; Zhang, Chengbin; Wang, Baogang; Wang, Xiaocong
Abstract : Aneurysms of the aortic sinus are well‐known clinical entities that can bulge into adjacent heart chambers or vessels. They usually reside in the right ventricle and very rarely bulge into the left ventricle causing mitral valve deformation. A 47‐year‐old man was admitted for shortness of breath and chest pain after exertion. He was diagnosed with a noncoronary sinus of Valsalva aneurysm bulging into the mitral valve's anterior leaflet. The aortic valve and mitral valve annulus were severely damaged and irreparable. A Bentall procedure and mechanical mitral valve replacement were performed. The patient recovered uneventfully and was discharged 11 days later.